2018
DOI: 10.2136/vzj2018.05.0104
|View full text |Cite
|
Sign up to set email alerts
|

Black Film Mulching and Plant Density Influencing Soil Water Temperature Conditions and Maize Root Growth

Abstract: Plastic mulch in combination with high plant density is a common agronomic technique in rainfed maize (Zea mays L.) production. However, the effects of combining colored film mulching and plant density on soil temperature, soil water storage, the maize roots, and yield have not been thoroughly elucidated to date. Thus, a field experiment to explore the effects of colored film mulching and plant density on soil temperature and water, maize roots, and yield was conducted on main plots with three types of mulchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
13
2
Order By: Relevance
“…Plant population density had no effect on RLD v and average root diameter against and between crop rows at V6 and VT (Tables 3 and 4). This is in contrast with findings of Sun, Chen, Jiang, and Zhang (2018), who reported that root diameter decreased as plant population increased. Maize root diameter is directly linked to the investment of biomass to its roots by each plant (Eissenstat, 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Plant population density had no effect on RLD v and average root diameter against and between crop rows at V6 and VT (Tables 3 and 4). This is in contrast with findings of Sun, Chen, Jiang, and Zhang (2018), who reported that root diameter decreased as plant population increased. Maize root diameter is directly linked to the investment of biomass to its roots by each plant (Eissenstat, 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…There is an important relationship between root growth and the photosynthetic products transported from the shoot (Ogawa et al, 2005). As planting density increases, root growth becomes inhibited, and the root length, surface area, and root activity decrease (Liedgens et al, 2000;Niu et al, 2010;Chen et al, 2012;Sun et al, 2018). Our field and soil column experiment results showed that senescence of lower leaves significantly reduced root biomass, root length, and root surface area in two maize varieties post-silking (Tables 2, 6).…”
Section: Discussionmentioning
confidence: 59%
“…In addition, principal component analysis (PCA) was used to reduce the dimension of meteorological factors with the criteria that the cumulative contribution was ≥85% and the eigenvalue was >1. If these criteria were satisfied, then the principal components (PCs) were selected to represent all meteorological information (Feng et al, 2018;Sun, Chen, Jiang, & Zhang, 2018). The multiple linear regression (MLR) method was then used to describe the impacts of the PCs and soil water contents on the evaporation properties of the different landscapes.…”
Section: Discussionmentioning
confidence: 99%